Answer:
Step-by-step explanation:
Through -3 , -2 slope = -2/3
y1 = -2 & x1 = -3 and m = -2/3
y - y1 = m(x - x1)
y - (-2) = -2/3(x - (-3))
y + 2 = -2/3(x + 3)
Multiply each term by 3
3y + 6 = -2(x + 3)
3y + 6 = -2x - 6
3y = -2x - 6 - 6
3y = -2x - 12
Answer:
hi I'm soooooo smart
Step-by-step explanation:
I'm smart
The y intercept is (0, 1)
Answer:
-5n + 8
Step-by-step explanation:
<u>1. What is the difference?</u>
The sequence goes down by 5. This means that the formula will have -5n in it.
<u>2. Work out the term before the first term.</u>
The first term is 3, and we know that the sequence goes up by 5. So, to get the term before 3 we would add 5.
3 + 5 = 8 Remember, this is positive 8. (+8)
<u>3. Put that term at the end of the equation. </u>
We have -5n already and we just worked out the term before the first one which is positive 8 - so put that at the end of the equation.
-5n + 8 This is our answer!
Just to prove it works:
<em>Substitute: n = term</em>
Lets see if we can get the 3rd term which is -7. (n = 3)
-5(3) + 8
-15 + 8 = -7
See, it works!
<span>So we need to explain how we know 21/30 is greater than 2/3. Well lets expand 2/3 by multiplying the numerator and the denumerator by 10. That way we get 20 / 30. Since 21/30 has 1/30 more than 20/30 we can clearly see that 21/30 is greater than 20/30 or 2/3.</span>